Nouveau traité d'instrumentation - Gevaert, François-Auguste Baron 1828-1908 (Paris Lemoine, 1885)
Classification et description des instruments, intonation
François-Auguste baron Gevaert (also Frans August Gevaert; 1828-1908) was a Belgian composer and organist. He is mainly remembered in music history as a music educator and conservatory director and as a musicologist, who published on music in antiquity, church music, orchestration and instrumentation.
Par F.-A. Gevaert. Directeur du Conservatoire Royal de Bruxelles. Maître de chapelle de S. M. la Roi des Belges, membre de l'Académie de Belgique, et de l'Institut de France
Keywords: Conservatoire royal de musique (Brussels, Belgium); 19th Century (1801-1900); Instrumentation; Brussels (Belgium)